Thermal annealing and transformation of dimer F centers in neutron-irradiated Al2O3 single crystals - Shablonin, Evgeni; Popov, Anatoli I.; Prieditis, G.; Vasil'Chenko, Evgeni A.; Lushchik, Aleksandr Ch (Elsevier B.V., 2021)
The precise study of the thermal annealing of the F2-type dimer defects, being under discussion in the literature for a long time and responsible for the number of absorption bands below 4.5 eV, has been performed in corundum single crystals irradiated by fast neutrons with a fluence of 6.9 × 1018 n/cm2. The Gaussian components of the radiation-induced optical absorption with the maxima at 4.08, 3.45 and 2.75 eV have been considered as a measure of the F2, F2+and F22+centers, respectively. In contrast to the Fand F+ centers, the concentration of which continuously decreases at the sample heating up to 1100 K, the concentration of dimer defects with different charge states passes the increasing stages above 500 K starting from the F22+centers. The tentative mechanisms of such rise of the F22+centers as well as of the subsequent transformation/rise of dimer centers, F22+→F2+→F2at 650-800 K are considered. The possible sources of carriers needed for the recharging of dimer centers are also analysed on the basis of thermally stimulated luminescence measurements up to ~850 K.
This work has been carried out within the framework of the EUROfusion Consortium and has received funding from the Euratom research and training programme 2014-2018 and 2019-2020 under grant agreement No 633053. The views and opinions expressed herein do not necessarily reflect those of the European Commission. In addition, the research leading to these results has received funding from the Estonian Research Council grant (PUT PRG619).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Dimer F-type centers; Radiation induced optical absorption; Irradiation by fast neutrons; Thermal annealing; α-Al2O3